ATTITUDES TOWARDS WASTE MANAGEMENT IN NABARI PAYAM SOUTH SUDAN. A CROSS-SECTIONAL STUDY - Aboor, Agaar Chep; Mubiru, Deng; Sendagi , Mohammed (Student’s Journal of Health Research Africa, 2025)
Background Countries need to have waste management policies that streamline the behaviors of residents on how best to practice and manage waste generated by different sources. The study aims to assess the attitude toward waste management in Nabari Payam South Sudan. Methodology A cross-sectional survey, descriptive and explanatory design where quantitative and qualitative methods were adopted. A questionnaire and Focus group discussion were adopted and interviews for Key Informants. Data was analyzed descriptively using the Statistical Package for Social Sciences and thematic methods for quantitative and qualitative data. Results 156 (46.7%) and 58 (17.4%) of the respondents disagreed and strongly disagreed that their Payam residents had done enough for waste management, the mean score was 2.37, and the standard deviation 1.01. For proper management of waste by the local authority, findings showed that 257 (76.9%) and 64 (19.2%) of the respondents disagreed and strongly disagreed, the mean was 1.91, and the standard deviation was 0.68. Regarding safety when handling waste, it was found that 246 (73.7%) of the respondents and 40 (12.0%) disagreed and strongly disagreed attracted a mean score of 2.51 and a standard deviation of 0.85. Conclusion Residents in Nabari Payam had a negative attitude towards waste management and there was dissatisfaction with provisions of waste material that were lacking and inadequate in the Payam. Recommendations Regular monitoring and evaluation of waste management activities at the Payam residents need to be geared up to have total adherence to introduced guidelines for waste management.